Mesoplankton across the North Atlantic: Composition and environmental drivers at 59.5th latitude. (October 2021) - Vedenin, A.; Anokhina, L.; Gladyshev, S.; Vereshchaka, A.
Abstract: North Atlantic zooplankton communities vary in terms of abundance, biomass and species composition depending on various environmental factors. In this study we analyzed the influence of hydrological factors (water temperature, salinity and density) on mesoplankton and retrieve boundaries between mesoplankton assemblages across the Subpolar North Atlantic. The material was collected in July 2013 with the use of Juday plankton net vertical hauls (0–300 m layer) at 55 stations arranged along a longitudinal transect along 59.5° N during the 41-th expedition of R/V "Akademik Ioffe". Both total abundance and biomass were higher in the eastern part of the transect and greatly decreased in the western part except the Greenland shelf and slope where the values were high. Four mesoplankton assemblages were retrieved by cluster analysis: two of them (above the Rockall Plateau and the Island Basin) were associated with warm Atlantic waters, the other two assemblages (in the Irminger Basin and above the Greenland slope and shelf) inhabited cold Arctic waters. The major biogeographic boundary was linked to the Subarctic Front above the Reykjanes Ridge. The best correlations of zooplankton characteristics with the surface chlorophyll a amount were obtained when averaging the surface chlorophyll data over May and 3 latitudinal and longitudinal degrees around each station. This can be connected to the main spring phytoplankton bloom, occurring during May in this area. The exception was the western-most part of the transect above the Greenland shelf and slope that harbored separate mesoplankton assemblages with high abundance and biomass, dominated by early mesoplankton stages (e.g. young copepodites and nauplii). These assemblages were likely supported by summer subsurface phytoplankton bloom caused by a water discharge from the melting Greenland Ice Shield. Highlights: The mesoplankton was studied across the North Atlantic along 59.5° N from the Rockall Plateau to South Greenland. Abundance and biomass values were higher in the eastern part of the transect and greatly decreased in the western part. Four mesoplankton assemblages were retrieved by cluster analysis. The major biogeographic boundary was linked to the Subarctic Front above the Reykjanes Ridge. The Greenland assemblages were likely supported by summer subsurface phytoplankton bloom.